FRUIT AND VEGETABLE CONSUMPTION, SEDENTARY ACTIVITIES, AND NUTRITION STATUS IN SENIOR HIGH SCHOOL STUDENTS DURING COVID-19 PANDEMIC: AN OBSERVATIONAL STUDY - Wisnuwardani, Ratih Wirapuspita; Cahyantari, Umi; Noviasty, Reny; Afiah, Nurul; Tri Agustini, Rina; Kurniawati, Eva R (The Indonesian Journal of Public Health, 2025)
Introduction: Adolescent health will impact future well-being. The COVID-19 pandemic has prompted governmental imposition of restrictions on social activities. Hence, understanding the lifestyle factors, such as sedentary activities and fruit and vegetable consumption, affecting adolescents' nutritional status during the pandemic is crucial. In Samarinda, more than 18% of adolescents have inadequate nutritional status. Aims: to explore the relationship between sedentary activities, fruit and vegetable consumption, and the nutritional status of adolescents. Method: Using an online questionnaire, a cross-sectional study was conducted on 300 high school students during the COVID-19 pandemic, between October and December 2021. Sedentary activity levels were assessed using the Adolescent Sedentary Activity Questionnaire (ASAQ), while fruit and vegetable consumption was evaluated through the FFQ-SQ (Food Frequency Questionnaire-Semi Quantitative). Nutritional status was determined using z score of body mass index (BMI) for age. Data analysis employed the Chi-square test and Fisher exact test. Results: Gender, maternal occupation, and average monthly parental income were found to be associated with nutritional status (p=0.020; p=0.038; p=0.045). However, no significant association was observed between fruit and vegetable consumption and nutritional status (p=0.102; p=0.121). Certain sedentary activities, such as doing assignments without using a laptop/computer (p=0.029) and reading for pleasure (p=0.038), were linked to nutritional status. Fruit and vegetable consumption showed no association with the nutritional status of adolescents. Conclusion: Conversely, certain sedentary activities were found to be associated with nutritional status. Educating adolescents within families and schools regarding the significance of physical activity and balanced nutrition is imperative.